Cpi2e: an interactive simulation game - Mohamad Zani, Nur Aniera Alieana; Mohamed, Suhana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
CPI2E is an interactive learning tool where it will be conducted as a simulation game. CPI2E is an engaging and fun way for students to learn how the Consumer Price Index (CPI), imports, exports, and GDP are connected. The game was made to make finance and economic ideas more interesting by modeling real-life situations in which students have to make choices based on changes in inflation and trade prices. The game stands out because it lets students learn by doing it in a fun and easy way that helps them understand how economic decisions affect the economy. It also teaches students how to think critically and solve problems, and generates an early interest in business by showing them how economic factors affect business choices. The game could be sold as an educational tool for schools or online learning sites. It would be a great way to teach finance and economic ideas in a more fun and interactive way.